Phytotreatment of soil contaminated with used lubricating oil using Hibiscus cannabinus - Abioye, O.P.; Agamuthu, P.; Abdul Raman, Abdul Aziz (2012)
Soil contamination by hydrocarbons, especially by used lubricating oil, is a growing problem in developing countries, which poses a serious threat to the environment. Phytoremediation of these contaminated soils offers environmental friendly and a cost effective method for their remediation. Hibiscus cannabinus was studied for the remediation of soil contaminated with 2.5 and 1 used lubricating oil and treated with organic wastes banana skin (BS), brewery spent grain (BSG) and spent mushroom compost (SMC) for a period of 90 days under natural conditions. Loss of 86.4 and 91.8% used lubricating oil was recorded in soil contaminated with 2.5 and 1% oil and treated with organic wastes respectively at the end of 90 days. However, 52.5 and 58.9% oil loss was recorded in unamended soil contaminated with 2.5 and 1% oil, respectively. The plant did not accumulate hydrocarbon from the soil but shows appreciable accumulation of Fe and Zn in the root and stem of H. cannabinus at the end of the experiment. The first order kinetic rate of uptake of Fe and Zn in H. cannabinus was higher in organic wastes amendment treatments compared to the unamended treatments, which are extremely low. The results of this study suggest that H. cannabinus has a high potential for remediation of hydrocarbon and heavy metal contaminated soil.